Opportunities of Homestay Tourism in Nepal: Study of Annapurna Rural Municipality-10, Ghandruk - Duwadi, Pampha (Rural Development Journal, 2026)
This study explores the potential of homestay tourism in Ghandruk, a picturesque village in the Annapurna region of Nepal, with the objective of facilitating meaningful interactions between tourists and local communities. By focusing on the sharing of local traditions and customs, the survey aims to assess the viability of homestays as a sustainable tourism model that promotes cultural exchange and economic benefits for the host community. The nature of the study is mixed, using purposive sampling method which is under the non-probability sampling. In this study 15 respondents were carried out in total. Ghandruk faces many challenges in homestay tourism but there are also great opportunities. Through a combination of surveys, interviews, and questionnaire with local families. The findings highlight Ghandruk’s rich cultural heritage, which presents a strong foundation for developing homestay tourism, providing both visitors and locals with unique opportunities to engage in authentic, immersive experiences. The paper concludes with recommendations for fostering community involvement, enhancing tourist experiences, and ensuring sustainable growth in Ghandruk’s homestay tourism sector.